A Pilot Study on Tocilizumab in Very-Late-Onset Myasthenia Gravis - Yang TT; Wang ZY; Fan ZX; Yuan BY; Ma L; Lu JF; Liu PJ; He Y; Liu GZ (Journal of Inflammation Research, 2023)
Ting-Ting Yang,1,* Ze-Yi Wang,1,* Ze-Xin Fan,1 Bo-Yi Yuan,1 Lin Ma,1 Jian-Feng Lu,1 Pen-Ju Liu,1 Yang He,2 Guang-Zhi Liu1 1Department of Neurology, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People’s Republic of China; 2Department of Neurology, Peking University People’s Hospital, Beijing, 100044, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guang-Zhi Liu, Department of Neurology, Beijing Anzhen Hospital, Capital Medical University, Beijing, 100029, People’s Republic of China, Tel +86-10-64456149, Fax +86-10-64456119, Email guangzhi2002@hotmail.comObjective: This study aimed to initially investigate the efficacy and safety of low-dose tocilizumab combined with glucocorticoid for the treatment of very-late-onset myasthenia gravis (VLOMG).Methods: We conducted a retrospective study in VLOMG patients who were administered intravenous methylprednisolone therapy and subsequently received low-dose oral corticosteroid, in combination with intravenous injection of tocilizumab given once every month for three months.Results: Five patients (mean age 75.0 ± 4.5 years) were included, and all of them were new-onset, and anti-acetylcholine receptor (AChR) antibody-positive generalized MG. The Quantitative Myasthenia Gravis Scale (QMGS) and Myasthenia Gravis Activities of Daily Living (MG-ADL) scores before treatment were 15.4 ± 4.3 and 9.6 ± 2.3, respectively, and they exhibited a continuously decreasing trend after the first, second, and third injection of tocilizumab until 6 months after treatment. At 6 months post-treatment, the QMGS and MG-ADL scores were 5.0 ± 2.9 and 2.0 ± 1.2, respectively, and the difference between scores at baseline and 6-month follow-up was significant (P = 0.005 and P < 0.0001, respectively). No serious adverse drug reactions were reported in any patient during the study period.Discussions and Conclusion: The therapeutic efficacy of tocilizumab in VLOMG remains uncertain. The results from our study support the efficacy and safety of this combination treatment option for VLOMG, and strongly suggests the therapeutic potential of tocilizumab in VLOMG. However, considering the limitation of retrospective nature and small sample size in this study, prospective randomized controlled studies including a larger sample size of selected patients are needed to validate our results.Keywords: very late-onset myasthenia gravis, immunotherapy, tocilizumab, glucocorticoid